2019
DOI: 10.1111/jora.12510
|View full text |Cite
|
Sign up to set email alerts
|

Teen Dating Violence Perpetration: Protective Factor Trajectories from Middle to High School among Adolescents

Abstract: Protecting adolescents from the risk of teen dating violence (TDV) perpetration is critical to enhancing prevention efforts. This study examined longitudinal trajectories of four protective factors (i.e., empathy, social support, parental monitoring, and school belonging) across adolescence in relation to four TDV types (i.e., verbal, relational, physical, and sexual). Adolescents (n = 1,668) who reported being in a relationship or dating during high school completed self‐report measures from middle through hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
1
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 60 publications
0
23
1
6
Order By: Relevance
“…Physical offline DV victimization could be a higher risk factor of cyber DV victimization for girls, who would also be more likely to suffer cyber-aggression and cyber-control by their partners, and with more serious consequences for their psychosocial adjustment. These differences between boys and girls highlight the need to take a gender perspective in teen dating violence research [22,65,66], as some differences appear in the variables related to different teen DV types in adolescent boys and girls. From this gender perspective, not only should the differences between boys and girls in the relations among variables be analyzed, but also new variables, such as the extent to which girls and boys assume female and male stereotypes, their gender identity or their adhesion to male and female social norms, should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Physical offline DV victimization could be a higher risk factor of cyber DV victimization for girls, who would also be more likely to suffer cyber-aggression and cyber-control by their partners, and with more serious consequences for their psychosocial adjustment. These differences between boys and girls highlight the need to take a gender perspective in teen dating violence research [22,65,66], as some differences appear in the variables related to different teen DV types in adolescent boys and girls. From this gender perspective, not only should the differences between boys and girls in the relations among variables be analyzed, but also new variables, such as the extent to which girls and boys assume female and male stereotypes, their gender identity or their adhesion to male and female social norms, should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…There are also a number of factors that act as protectors against TDV, such as close friendships and conditional tolerance for violence [ 13 ]; or studies that point to a greater risk prediction in experiences of victimisation in the relationship of couples belonging to sexual minority groups [ 14 ]. In terms of predicting the perpetration of dating violence, it is important to study factors such as empathy, social support, parental monitoring and school membership [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this developmental period, courtship behavior develops, and the risk of teen dating violence (TDV) perpetration and/or victimization emerges [ 2 ]. Various studies have indicated that violence towards a partner peaks in adolescence [ 3 , 4 ]. A 10-year longitudinal study [ 5 ] on men’s aggression over time found a downward linear relationship between age and physical violence perpetration, regardless of changes in relationships.…”
Section: Introductionmentioning
confidence: 99%
“…Operationalization of the different types of TDV is seen in commonly used scales, such as the Revised Conflict Tactics Scales-2 (CTS2) [ 10 ] and the Conflict in Adolescent Dating Relationships Inventory (CADRI) [ 9 ]. Each scale uses multiple items to generate different subscales for the distinct forms of abuse, recognizing their equal contributions to TDV as a whole [ 3 , 11 ]. In contrast, some studies use single items to assess for abuse (e.g., physical abuse) embedded within a questionnaire [ 12 ].…”
Section: Introductionmentioning
confidence: 99%